Помогите пожалуйста (х-3)(х-2)=7х-1

Помогите пожалуйста (х-3)(х-2)=7х-1
Гость
Ответ(ы) на вопрос:
Гость
Выражение: (X-3)*(X-2)=7*X-1 Ответ: X^2-12*X+7=0 Решаем по действиям:1. (X-3)*(X-2)=X^2-5*X+6  (X-3)*(X-2)=X*X-X*2-3*X+3*2  1.1. X*X=X^2      X*X=X^(1+1)    1.1.1. 1+1=2          +1           _1_           2  1.2. -X*2-3*X=-5*X  1.3. 3*2=6      X3       _2_       62. -5*X-7*X=-12*X3. 6+1=7  +6   _1_   7 Решаем по шагам:1. X^2-5*X+6-7*X+1=0  1.1. (X-3)*(X-2)=X^2-5*X+6      (X-3)*(X-2)=X*X-X*2-3*X+3*2    1.1.1. X*X=X^2          X*X=X^(1+1)      1.1.1.1. 1+1=2              +1               _1_               2    1.1.2. -X*2-3*X=-5*X    1.1.3. 3*2=6          X3           _2_           62. X^2-12*X+6+1=0  2.1. -5*X-7*X=-12*X3. X^2-12*X+7=0  3.1. 6+1=7      +6       _1_       7
Не нашли ответ?
Ответить на вопрос
Похожие вопросы